FUNGSI SCHEMA DALAM DATABASE MANAGEMENT SYSTEM INFORMASI PADA DATA ARCHITECTURE (Kohesi: Jurnal Sains dan Teknologi, 2025)
Lack of understanding of the schema function in database systems leads many organizations to struggle in managing data efficiently and securely. This study aims to examine the critical role of schema in supporting database structure and data architecture. The method used is qualitative with a literature study approach, by collecting and analyzing various scientific sources related to schema concepts, data security, consistency, and system scalability. The findings show that schema functions as a fundamental design in databases, helping maintain data integrity, regulate access control, and support system migration and development. With proper schema design, data management becomes more organized, efficient, and adaptive to technological developments.  Keywords: Schema, Database, Data Architecture